Ciliary disturbances in syndromal and non-syndromal obesity - de Vries, Tamar I.; van Haelst, Mieke M. (Journal of Pediatric Genetics, 2014)
Obesity is an increasing global health problem. Although it is mainly thought to be due to the changing obesogenic environment, the genetic contribution has been estimated between 40–70%. A number of genes have been identified that cause obesity in animals as well as in humans. Rare highly penetrant monogenic forms of obesity can cause both syndromal and non-syndromal forms of obesity. Bardet-Biedl syndrome and Alström syndrome are well known monogenic obesity syndromes caused by primary cilia defects. The pathogenesis of the obesity phenotype in these disorders is however not fully understood. Disturbance of the appetite regulation system, abnormalities in body composition and decreased energy expenditure have been suggested to cause obesity in these ciliopathies. There are currently 19 known genes associated with Bardet-Biedl syndrome and one Alström syndrome gene. Although ciliopathy genes have been described primarily in these syndromal obesity disorders, non-syndromal obesity may also result from disturbed cilia function. There are multiple genes associated with both obesity and ciliary function. Here we provide an overview of the current knowledge of the clinical, pathophysiological and genetic aspects of obesity in patients with ciliary defects.
Keywords: Obesity; ciliopathy; Bardet-Biedl syndrome; Alström syndrome; genetics